2022
DOI: 10.21203/rs.3.rs-999738/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bipolar Cell Targeted Optogenetic Gene Therapy Restores Parallel Retinal Signaling And High-Level Vision In The Degenerated Retina

Abstract: Optogenetic gene therapies to restore vision are in clinical trials. Whilst current clinical approaches target the ganglion cells, the output neurons of the retina, new molecular tools enable efficient targeting of the first order retinal interneurons, the bipolar cells, with the potential to restore a higher quality of vision. Here we investigate retinal signaling and behavioral vision in blind mice treated with bipolar cell targeted optogenetic gene therapies. All tested tools, including medium-wave opsin, O… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…While the bRhod-b2AR variant was optimally designed by introducing the b2AR TM5-IL3-IL6 and C-terminus after the palmitoylation site in bRhod, a proximal C-terminus replacement of melanopsin by the whole C-terminus of the mGluR6 receptor, including the proximal C-terminus, sufficed to retarget to the Gi/o protein class. Overall, the Mela(palm)-mGluR6(CT) seems to be the favorable chimera for functional applications since it activates G-proteins with high efficacy and shows a strong tropism towards Gi/o (Kralik et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the bRhod-b2AR variant was optimally designed by introducing the b2AR TM5-IL3-IL6 and C-terminus after the palmitoylation site in bRhod, a proximal C-terminus replacement of melanopsin by the whole C-terminus of the mGluR6 receptor, including the proximal C-terminus, sufficed to retarget to the Gi/o protein class. Overall, the Mela(palm)-mGluR6(CT) seems to be the favorable chimera for functional applications since it activates G-proteins with high efficacy and shows a strong tropism towards Gi/o (Kralik et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While the bRhod-b2AR variant was optimally designed by introducing the b2AR TM5-IL3-IL6 and C-terminus after the palmitoylation site in bRhod, a proximal C-terminus replacement of melanopsin by the whole C-terminus of the mGluR6 receptor, including the proximal C-terminus, sufficed to retarget to the Gi/o protein class. Overall, the Mela(palm)-mGluR6(CT) seems to be the favorable chimera for functional applications since it activates G-proteins with high efficacy and shows a strong tropism towards Gi/o (Kralik et al, 2022). Of course, since Cryo-EM studies on mGluR2 showed that the G-protein’s C-terminus is stabilized by a pocket formed by IL2 and the C-terminus (Seven et al, 2021), IL2 may also be involved in Gi/o-selectivity together with the proximal C-terminus of mGluR6, which was, however, not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation